1998
DOI: 10.1097/00004836-199800001-00025
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection in the Remnant Stomach After Gastrectomy: With Special Reference to the Difference Between Billroth I and II Anastomoses

Abstract: Helicobacter pylori infection is associated with many gastric diseases, such as peptic ulcer and gastric cancer. We examined the remnant stomach for H. pylori infection after gastrectomy for gastric cancer or peptic ulcer between October 1992 and July 1997. H. pylori DNA in the gastric juice of 109 patients [mean age 62.4 years, male/female 78/31, gastrectomy for gastric cancer 83/peptic ulcer 26, Billroth I (BI) anastomosis 72/Billroth II (BII) 37, mean postoperative interval 6.0 years] was amplified by PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 15 publications
1
26
0
1
Order By: Relevance
“…We believe that this congruity occurred because the control group was of the same socioeconomic status as the patients in the literature. The prevalence of H. pylori in gastrectomized patients varies according to several factors; such as the postoperative period, the technique employed, and the age of the patient [19][20][21][22]. The prevalence of H. pylori in Billroth I gastrectomized patients varies from 36.9% to 80.3% [5,19,20], while that in Billroth II gastrectomized patients varies from 0% to 58% [19,20,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that this congruity occurred because the control group was of the same socioeconomic status as the patients in the literature. The prevalence of H. pylori in gastrectomized patients varies according to several factors; such as the postoperative period, the technique employed, and the age of the patient [19][20][21][22]. The prevalence of H. pylori in Billroth I gastrectomized patients varies from 36.9% to 80.3% [5,19,20], while that in Billroth II gastrectomized patients varies from 0% to 58% [19,20,23].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of H. pylori in gastrectomized patients varies according to several factors; such as the postoperative period, the technique employed, and the age of the patient [19][20][21][22]. The prevalence of H. pylori in Billroth I gastrectomized patients varies from 36.9% to 80.3% [5,19,20], while that in Billroth II gastrectomized patients varies from 0% to 58% [19,20,23]. There are few references in the literature concerning H. pylori and Roux-en-Y diversion; however, this technique could provide a high prevalence rate having in mind that biliary reflux is damaging to H. pylori [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover the colonization by H. pylori is disturbed by bile reflux after gastrectomy, especially after Billroth-II reconstruction. 12 According to most reports of the coexistence of adenocarcinoma and lymphoma, the lymphoma usually tends to be at an advanced stage and therefore, the prognosis of these patients chiefly depends on the stage of the lymphoma. 10,11 On the other hand, Nakamura et al reported that the survival probability for patients with double tumors appeared to be similar to that for patients with only gastric carcinoma; however, it was significantly worse than that for patients with only primary gastric lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Resection with B-I reconstruction shows an incidence of H. pylori infection of approximately 70%, followed by a significantly lower rate of infection in B-II anastomosis of 45% [71]. The lower rate of H. pylori infection found in B-II stomachs may reflect the role of bile reflux, which is more common in B-II than B-I and has been shown to interfere with the colonization by H. pylori.…”
Section: Relevance Of H Pylori Infections Following Surgical Treatmentmentioning
confidence: 97%